Effects of Indigenous Mulches on Growth and Yield of Tomato - Kayum, MA; Asaduzzaman, M; Haque, MZ (Journal of Agriculture & Rural Development, 2008)
Three popular tomato varieties namely, Ratan, BARI tomato-3 and BARI tomato-6 were experimentally evaluated to identify the potential mulch on growth and yield, where the experiment consisted of four mulching treatments viz. water hyacinth, straw, am-ada leaf and banana leaf with a control (no mulch). The experiment was conducted under rainfed condition. In the experiment, mulching showed significant effect on growth, yield components and thus on the yield of tomato. Yield contributing characters were significantly higher when water hyacinth mulch was used. The variety Ratan produced the highest (53.74 t/ha) fruit yield, while BARI tomato-3 showed the lowest (48.89 t/ha) fruit yield. The combination of mulching and variety exhibited significant variation in some yield components and yield. The combination of water hyacinth and Ratan produced the maximum yield (62.16 t/ha) and thus the experiment revealed that water hyacinth and straw mulches have potentiality to increase the yield of tomato. Key words: Indigenous mulch, growth, yield, tomato. doi:10.3329/jard.v6i1.1650 J Agric Rural Dev 6(1&2), 1-6, June 2008